Trigger Point Injections for Pelvic Floor Myofascial Spasm Refractive to Primary Therapy. Issue 2 (2017) - Fouad, Lina S.; Pettit, Paul D.; Threadcraft, Marcus; Wells, Ali; Micallef, Audrey; Chen, Anita H.
Introduction: A retrospective chart review was conducted of visual analog scale (VAS) scores completed before and after trigger point injections (TPIs) for pelvic floor myofascial spasm to evaluate response. Methods: Sixty-eight female patients who underwent TPIs from October 9, 2007 to March 12, 2015 were included. The primary end point was the difference between scores. Secondary analyses were conducted for patients who needed repeat TPIs. Descriptive and paired t test analyses were used. Results: The key result was an improvement in VAS scores for 65% (44/68) of patients (p<0.0001). The median pre-injection VAS score was 7 (1 to 10), (mean 6.3). The median post-injection VAS score was 4 (0 to 9), (mean 4.3). The median difference between scores in patients who improved was 3 (1 to 8), (mean 3.6). Seventeen of 68 (25%) patients needed repeat TPI, and the median time between injections was 1.5 months (1 to 7 months), (mean 2.2 months). When analyzing pre-injection VAS scores in patients who underwent subsequent repeat injection when compared to patients who did not require repeat injection, there was no difference (p = 0.32). In addition, the differences between pre- and post-injection VAS scores in the patients who underwent repeat injection and those who did not was not significant (p = 0.26). Conclusions: We report on 68 women who underwent TPIs, with an improvement in VAS pain scores in 65%. It appears that TPIs for pelvic floor myofascial spasm are successful in reducing pain scores for patients who are refractory to primary therapy.